2022 10th RSI International Conference on Robotics and Mechatronics (ICRoM) 2022
DOI: 10.1109/icrom57054.2022.10025211
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Slalom Maneuver Based on Expert Drivers’ Behavior Using Convolutional Neural Network

Abstract: Lane changing and obstacle avoidance are one of the most important tasks in automated cars. To date, many algorithms have been suggested that are generally based on path trajectory or reinforcement learning approaches. Although these methods have been efficient, they are not able to accurately imitate a smooth path traveled by an expert driver. In this paper, a method is presented to mimic drivers' behavior using a convolutional neural network (CNN). First, seven features are extracted from a dataset gathered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Imitation learning is one of the earliest and most successful methods for Autonomous Driving tasks. Authors in [16], [17], and [18] have used different variations of Imitation Learning to solve overtaking or lane changing specifically.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Imitation learning is one of the earliest and most successful methods for Autonomous Driving tasks. Authors in [16], [17], and [18] have used different variations of Imitation Learning to solve overtaking or lane changing specifically.…”
Section: Related Workmentioning
confidence: 99%
“…Authors in [19] showed that using a long short-term memory (LSTM) module for Lane Change (LC) prediction achieves a significant improvement in both adaptive cruise control (ACC) and cooperative adaptive cruise control. In another work [18], the authors used a convolutional neural network (CNN) to show that this network is capable of learning the expert policy excellently.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation